2016
DOI: 10.1016/j.otsr.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Total elbow arthroplasty for primary and metastatic tumor

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 20 publications
3
55
0
3
Order By: Relevance
“…The search strategy identified 49 studies eligible for inclusion (n ¼ 1995); 10 on inflammatory arthritis (n ¼ 773), [13][14][15][16][17][18][19][20][21][22] 8 following acute fractures (n ¼ 179), [23][24][25][26][27][28][29][30] 10 on post-trauma sequelae (n ¼ 216) 26,31-39 4 for miscellaneous indications (n ¼ 82), [40][41][42][43] 17 reporting on multiple indications (n ¼ 724) [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and 1 on OA (n ¼ 18). 61 This included one study that reported on separate subgroups of acute fractures and in post-trauma sequelae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy identified 49 studies eligible for inclusion (n ¼ 1995); 10 on inflammatory arthritis (n ¼ 773), [13][14][15][16][17][18][19][20][21][22] 8 following acute fractures (n ¼ 179), [23][24][25][26][27][28][29][30] 10 on post-trauma sequelae (n ¼ 216) 26,31-39 4 for miscellaneous indications (n ¼ 82), [40][41][42][43] 17 reporting on multiple indications (n ¼ 724) [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and 1 on OA (n ¼ 18). 61 This included one study that reported on separate subgroups of acute fractures and in post-trauma sequelae.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported on miscellaneous indications for TEA [40][41][42][43] Two studies reported the use of Coonrad-Morrey in patients with a mixture of primary and metastatic tumours with the age of patients varying from 9 to 86 years in a wide variety of tumours. Mean follow-up in both studies was under three years.…”
Section: Miscellaneous Indicationsmentioning
confidence: 99%
“…По данным литературы, невропатия может возникать у 25% пациентов. Восстановление утраченной неврологической функции происходит в сроки от 6 месяцев до 1 года [9]. В нашем исследовании сроки восстановления чувствительности были сопоставимы с данными литературы.…”
Section: результаты исследования и обсуждениеunclassified
“…По данным литературы, воспалительные процессы могут возникать примерно в 9% случаев [9]. В нашем исследовании у 1 пациента (…”
Section: результаты исследования и обсуждениеunclassified
See 1 more Smart Citation